Circulating adrenal 11-oxygenated androgens are associated with clinical outcome in endometrial cancer - Dahmani, Cylia; Caron, Patrick; Simonyan, David; Turcotte, Véronique; Grégoire, Jean; Plante, Marie; Guillemette, Chantal (Frontiers in Endocrinology, 2023)
Context: Recent evidence support that androgens play an important role in the etiology of endometrial cancer (EC). Adrenal-derived 11-oxygenated androgens are highly potent agonists of the androgen receptor (AR), comparable to testosterone (T) and dihydrotestosterone (DHT) that have not been studied in the context of EC. Methodology: We studied a cohort of 272 newly diagnosed postmenopausal EC cases undergoing surgical treatment. Circulating concentrations of seven 11-oxygenated androgens including precursors, potent androgens and their metabolites were established in serum samples collected before and 1 month after surgery using a validated liquid chromatography tandem mass spectrometry method (LC-MS/MS). Free (unconjugated) and total (free + sulfate and glucuronide conjugates following enzymatic hydrolysis) were analyzed in relation to clinicopathological features, recurrence and disease-free survival (DFS). Results: Levels of 11-oxygenated androgens were weakly correlated to those of canonical androgens such as testosterone (T) and dihydrotestosterone (DHT), with no evidence of their association with clinicopathological features. Levels of 11-oxygenated androgens declined after surgery but remained higher in overweight and obese compared to normal weight cases. Higher levels of preoperative free 11-ketoandrosterone (11KAST) were associated with an increased risk of recurrence (Hazard ratio (HR) of 2.99 (95%CI=1.09-8.18); P=0.03). Postoperative free 11β-hydroxyandrosterone (11OHAST) levels were adversely associated with recurrence and DFS (HR = 3.23 (1.11-9.40); P=0.03 and 3.27 (1.34-8.00); P=0.009, respectively). Conclusion: 11-oxygenated androgen metabolites emerge as potential prognostic markers of EC.